A simplistic approach to detect health anomalies at a regional level using shrimp production data - Ana Muniesa; Julio Cabanillas‐Ramos; Imanol Ruiz‐Zarzuela; Francisco J. Magallón‐Barajas; Ignacio de Blas (Reviews in Aquaculture, 2018)
The global production and yield of shrimp ponds depend on multiple factors, and an unexpected variation in production parameters could be an indicator of pathological events such as white spot disease (WSD) outbreaks in a syndromic surveillance system. Using the production data from 7139 production cycles at farm level collected at two Mexican states (Sonora and Sinaloa) from 2004 to 2011, an ecological survey (also called correlational study) has been carried out summarizing data for year and oceanic basin. The production results had been analysed looking for significant association ( P